Synthesis of Some Carboxylate Tetraethylammonium Salts as Ionic Liquids - Mahmood, Muna Raad; Shihab, Mehdi Salih (Al-Nahrain Journal of Science, 2024)
Some of organic ammonium salts, namely: 2-((4-carboxyphenyl) carbamoyl) benzoate tetraethylammonium, B1, 4-oxo-4-(pyridin-3-ylamino)-2-butenoate tetraethylammonium, B2, 2-((4-carbamoylphenyl) carbamoyl) benzoate tetraethylammonium, B3, 4-((4-carbamoylphenyl)amino)-4-oxobutanoate tetraethylammonium, B4, are successfully synthesized as ionic liquids. By spectral techniques of FTIR, 1H-NMR and 13C-NMR the structures of organic salts are confirmed. The thermal analysis by differential scanning calorimetry (DSC) has shown the thermal stability of the organic ammonium salts (B1-B4). A high conductivity characteristic as compared with that of NaCl has been detected in the aqueous solution.